Engineered nanomaterials for overcoming multifaceted gastrointestinal barriers: Toward precision oral delivery of therapeutics - Yuxin Liu; Chengfei Liu; Dongyu An; Shiming Deng; Guijin Liu (Pharmacological Research)
Oral administration remains the preferred route for therapeutics due to its non-invasiveness and high patient compliance. However, its application for biologics (e.g., peptides, proteins, nucleic acids) and some small-molecule drugs is severely constrained by multifaceted gastrointestinal (GI) barriers. These barriers include chemical degradation, mucus entrapment, epithelial impermeability, first-pass metabolism, and gut microbiota interactions, which severely limit the oral bioavailability of most therapeutics. Engineered nanomaterials have emerged as revolutionary platforms, leveraging tunable physicochemical properties and bioresponsive functionalities to sequentially overcome GI barriers. Advanced systems using lipid-based, polymer-based, inorganic, and hybrid nanomaterials synergize sequential barrier evasion through integrated protection, mucus penetration, and receptor-targeted transcytosis. Despite preclinical success, challenges in rational material design, precise construction and safety concerns hinder their clinical translation. This review comprehensively analyzes the interplay between nanomaterial engineering and GI barrier evasion, providing a roadmap for advancing precision oral therapeutics from bench to bedside.